A cluster quasi-randomized controlled trial of an interactive, monthly obstetric anesthesiology curriculum: impact on resident satisfaction and knowledge retention. (February 2021) - Ende, H.B.; Lumbreras-Marquez, M.I.; Farber, M.K.; Fields, K.G.; Tsen, L.C.
Highlights: A study of resident didactic teaching of obstetric anesthesiology was performed. A lecture-based curriculum was compared with an interactive curriculum. Interactive curriculum used problem-based learning, simulation, literature reviews. The primary outcome was resident satisfaction with the curriculum. No difference in resident satisfaction with the curriculum between the two formats. Abstract: Background: Increasingly, evidence supports the use of educational paradigms that focus on teacher-learner interaction and learner engagement. We redesigned our monthly obstetric anesthesia resident didactics from a lecture-based curriculum to an interactive format including problem-based learning, case discussion, question/answer sessions, and simulation. We hypothesized that the new curriculum would improve resident satisfaction with the educational experience, satisfaction with the rotation, and knowledge retention. Methods: Fifty-three anesthesiology residents were prospectively recruited and quasi-randomized through an alternating-month pattern to attend either interactive sessions or traditional lectures. Residents completed a daily satisfaction survey about quality of teaching sessions and a comprehensive satisfaction survey at the conclusion of the rotation. Knowledge retention was assessed with a knowledge test completed on the final day. The primary outcome was daily satisfaction with the curriculum, and secondary outcomes included overall satisfaction with the curriculum, overall rotation satisfaction, and within-resident difference between pre- and post-knowledge test scores. Results: No differences were observed in daily resident satisfaction after interactive sessions vs traditional lectures. Furthermore, no differences were observed between the interactive sessions and traditional lecture groups in overall satisfaction with the curriculum, overall satisfaction with the entire rotation or within-resident difference between pre- and post-knowledge test scores. Conclusions: Our study failed to demonstrate improvement in resident satisfaction or knowledge retention following implementation of an interactive curriculum on a month-long obstetric anesthesia rotation. Reasons may include misalignment of the intervention with measured study outcomes, lack of sensitivity of the survey tools, and inadequate training of faculty presenters.